Fatma’s Dilemma: Sexual Crime and Legal Culture in an Early Modern Ottoman Court - P. Peirce, Leslie (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2003)
This essay studies the ways in which a seemingly powerless peasant girl is able to affect the legal environment of her provincial society. While the spareness of the court record prevents us from knowing all the details of this unmarried, pregnant girl’s story, we are justified, I argue, in viewing her as an intelligent architect of her own social fate. Fatma’s dilemma is placed within the shifting terrain of economic recovery and its consequent effects on young people’s ability to make marriages, of legal reform and its repercussions among the residents of a large village, and of the subtle but perceptible changes in the culture of Aintab court that affected her dilemma.